TRADITIONAL AND MODERN RELATIONS IN UZBEK FAMILIES - Nurmanov Shahzodbek Mahmadoli o`g`li (Western European Studies, 2024)
The family and the processes associated with it have always been a topical issue in ethnography. Because the family of each nation is different from each other with its own characteristics. In particular, Uzbek families have their own way of life and culture. When studying the kinship, family and marriage relations in Uzbek families, we observe the signs of tradition and modernity in these relations. When studying the kinship, family and marriage relations in Uzbek families, we observe the signs of tradition and modernity in these relations. The basis of kinship in families is the couple, children and the group of relatives closest to the family. That is why kinship relations, which have been developing in Uzbek families for a long time, are becoming modern. Because as family relationships and the traditions associated with them develop, so do kinship relationships.
Keywords: Family; marriage; tradition; kinship